PENGARUH PENERAPAN MODEL PROBLEM BASEDINTRUCTION(PBI) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X MAN KAJAI KEC. TALAMAU KAB. PASAMAN BARATTAHUN PELAJARAN 2013/ 2014 - Asmi, Melisa; Cesaria, Anna; Pratiwi, Merina (Pendidikan Matematika, 2014)
ABSTRACTThis research was based on the the studentsâ low understanding of mathematical concept and the studens still notÂ Â  commonly involved in problem solving. The purpose of this research wasto know what are the studentâs understanding of mathematical concept by usingPBI learningbetter than studentâs understanding of mathematical concept by using conventional learning. This was an experimental research which used random toward the subject design. The research population was a class X student of MAN Kajai Kec. Talamau Kab. Pasaman Barat. Sample of the research was X.A as experimental class and X.B as control class. The instrument used is an essay test with reliability 0,96. The techniques of data analysis were done to used the t-test a side. Based on analysis result Tvaluewas 1,792 and Ttable was 1,710 then the hypothesis in this research was accepted. Therefore it was concluded that the studentsâ understanding of mathematical concept by usingPBI Â learningÂ  better than the studentsâ understanding of mathematical concept by using conventional learning in class X MAN Kajai Kec. Talamau Kab. Pasaman Barat